The nationality of corporate investors under international investment law - Yilmaz Vastardis, Anil (Oxford, England : Hart Publishing, Bloomsbury Publishing Plc, 2020)
"This monograph offers a detailed and distinctive analysis of corporate nationality under international investment law, covering the ICSID Convention and the investment treaty framework. It takes the reader back to the basics threading through the concepts of jurisdiction, nationality, and corporate personality to give a clear context to the discussion of corporate nationality under international investment law, at a time when international investment is dominated by multinational business enterprises operating in a globalised economy. The book examines different understandings of corporate personality and nationality under a selection of major jurisdictions and public international law. It also offers an in-depth analysis of approaches found in ICSID arbitral awards and in investment treaty practice, distilling the problematic areas and discussing the impacts of the areas of concern. It evaluates the techniques developed to address problems and puts forward suggestions for effective and balanced solutions to the questions of corporate nationality and personal scope of investment protection"--
Access to international investment protection : ICSID, investment treaties and institutional arbitration rules -- Nationality as a legal bond in international law : a story of disagreement over the relevance and meaning of 'genuine link' -- Distinguishing features of corporations for purposes of nationality -- Corporate nationality in the context of diplomatic protection and war-time sanctions -- Corporate investors' nationality under the ICSID convention and investment treaties -- Exposing the fault line -- Evaluation of responses to nationality shopping and the way forward.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Investments, Foreign (International law); Corporations -- Investor relations; International commercial arbitration; International economic & trade law; Electronic books